Analisis Efektivitas Penggunaan Dana Bos dalam Laporan Keuangan Sekolah Al-Ishlah Kota Gorontalo - Mohamad Abdullah; Yuwin Ali; Mentari Ariesta Iyonu (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This research evaluates the effectiveness of School Operational Assistance (BOS) fund utilization at Al-Ishlah School, Gorontalo City, using a descriptive qualitative approach. The management of BOS funds has successfully supported operational expenses, educational accessibility, and learning quality improvements in accordance with the Ministry of Education and Culture Regulation Number 8 of 2020. Nevertheless, field findings indicate that the effectiveness indicator of timeliness remains suboptimal due to a 2-3 month delay in fund disbursement from the central government, which directly impacts the postponement of priority programs and financial reporting schedules. Overall, the other three indicators—accuracy of measurement, cost calculation, and target accuracy—have been effectively implemented through priority-based planning and disciplined monitoring. To mitigate these disbursement delays, the school is encouraged to strengthen internal fund allocation mechanisms, while the government is urged to streamline the bureaucratic system of fund distribution to ensure the continuity of educational operations.